El síndrome de alienación parental y la violación del derecho a mantener relaciones parento-filiales - González Pesantez, Milena Elizabeth (2017)
The primary purpose of this research is to present a legal argument regarding the need to regulate Parental Alienation Syndrome in the Organic Code of Childhood and Adolescence (CONA) in order to guarantee the right to maintain parent-child relationships. Therefore, to carry out this research, it was necessary to systematize it into three parts: the first, called the theoretical framework, which addresses the origin, conceptualizations, and critical assessment of the proposed problem, concluding with the conclusions reached; the second, called the Methodological Framework, in which various methods, techniques, and research instruments, such as surveys and interviews, were used, which served as the basis for substantiating the proposed proposal and also allowed for the diagnosis of existing problems; And finally, its third part, called the propositional framework, presents the legal arguments raised, providing a solution to the legal problem. It concludes with expert validation and the social and legal impact that the proposal would have. General conclusions and recommendations have also been made. It has been determined that Parental Alienation Syndrome needs to be classified as a classification in Family and Childhood legislation